Examining Anxiety and Depression among Undergraduate Nursing Students: A Cross-Sectional Study - Tazveen Fariha; Jalal Uddin; Jason D. Flatt (BioMed Target Journal)
Mental health is a crucial aspect of well-being, especially among undergraduate nursing students. Nursing students face unique stressors that can impact their mental health. This study aimed to determine the anxiety and depression levels among undergraduate nursing students at Chattogram, Bangladesh. A cross-sectional study design was employed, and data were collected using an online questionnaire (Google form) that included the Hospital Anxiety and Depression Scale (HADS). Convenience sampling was used to select 124 BSc Nursing students aged over 18 years. Data analysis was conducted using SPSS version 28. The majority of participants were female (88.3%), and the mean age was 20.58 years, range 18 to 23. The prevalence of anxiety was 66.0%, with 28.0% scoring in the borderline abnormal range and 38.0% in the abnormal range. For depression, 22.4% were in the borderline abnormal range, and 18.4% were in the abnormal range. Pearson correlation test showed gender was significantly associated with anxiety (p = 0.004). At the same time, no significant associations were found between depression and gender, depression and academic qualifications, contagious disease status, or close family members' infection status. The logistic regression analysis reveals that age is significantly associated with depression among nursing students; older students have higher odds of experiencing depression (OR = 1.384, p = 0.037). This study highlights a significant burden of anxiety among undergraduate nursing students at CINC, with a substantial proportion experiencing abnormal levels of anxiety. The findings underscore the importance of addressing mental health issues among nursing students and implementing strategies to promote their mental well-being.